2011
DOI: 10.1124/dmd.111.038125
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Blood Drug Concentrations and a Potential Relationship to Vitamin D

Abstract: ABSTRACT:The most important enzyme in hepatic drug metabolism is cytochrome P450 3A4. Published in vitro data indicate that vitamin D may up-regulate the expression of the CYP3A4 gene. Individual vitamin D levels are highly dependent on sunlight exposure and show great seasonal variability in northern countries. The aim of the present study was to investigate whether plasma concentrations of CYP3A4 drug substrates exhibit seasonal changes compatible with a stimulatory effect of vitamin D on drug metabolism. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 19 publications
4
47
0
Order By: Relevance
“…Taken together, we hypothesized that CYP3A4 expression and the corresponding drug-metabolizing capacity might display cyclic changes over the different seasons. Indeed, in a retrospective study on a large patient material from therapeutic drug monitoring, we were able to show such cyclic, seasonal variability in blood levels of the important immunosuppressants tacrolimus and sirolimus, known to be metabolized by CYP3A4 (Lindh et al, 2011). Significantly lower concentration-to-dose ratios were evident during the months of peak vitamin D levels, July-September, compared with December through February (Lindh et al, 2011).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Taken together, we hypothesized that CYP3A4 expression and the corresponding drug-metabolizing capacity might display cyclic changes over the different seasons. Indeed, in a retrospective study on a large patient material from therapeutic drug monitoring, we were able to show such cyclic, seasonal variability in blood levels of the important immunosuppressants tacrolimus and sirolimus, known to be metabolized by CYP3A4 (Lindh et al, 2011). Significantly lower concentration-to-dose ratios were evident during the months of peak vitamin D levels, July-September, compared with December through February (Lindh et al, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, in a retrospective study on a large patient material from therapeutic drug monitoring, we were able to show such cyclic, seasonal variability in blood levels of the important immunosuppressants tacrolimus and sirolimus, known to be metabolized by CYP3A4 (Lindh et al, 2011). Significantly lower concentration-to-dose ratios were evident during the months of peak vitamin D levels, July-September, compared with December through February (Lindh et al, 2011). This original finding raised several important questions, for example whether the individual vitamin D status is predictive of CYP3A4 activity and if treatment of patients with vitamin D results in higher CYP3A4-dependent drug metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CYP3A5*3 difference is in some different degree, and influence on C0 and CsA daily dosing, it seems genetic variation has little effect on the acute rejection rate in kidney transplant recipient (95). Environmental combined genetically factors also play an important role; literatures have shown that vitamin D may up-regulate the expression of the CYP3A4 gene and patient vitamin D low levels is highly in need of on sunlight and show excessive geographical and seasonal inconsistency (93). It revealed that sensitivity to CsA has inter-individual difference, and is higher in transplant recipients than in normal controls.…”
Section: Individualizing Target Range and Adjusting Dose Of Cyclosporinementioning
confidence: 99%
“…Also, CsA metabolites and their different organ delivery may possibly be another reasons (92). Additionally, enzymes are responsible; the most important enzyme in CsA hepatic metabolism is cytochrome P450 3A4 (93). It showed that a CsA level is mainly influenced by CYP3A4, CYP3A5 and MDR-1 genes.…”
Section: Individualizing Target Range and Adjusting Dose Of Cyclosporinementioning
confidence: 99%